ANALISIS TERHADAP STRATEGI PEMASARAN PRODUK UMRAH BAYAR KRIDIT PERSPEKTIF EKONOMI ISLAM (Studi Pada Risma Tour Banjarbaru) - Mardini, Yulida (Jurnal Hadratul Madaniyah, 2023)
This research was motivated by the  latest umrah service product from Risma Travel Banjarbaru which applies umrah packages with a credit (debt) system. While in Islam it is forbidden to perform Umrah in a state of debt. The product is interesting to be further researched and reviewed from the perspective of Islamic economics. The formulation of the problem in this study is: (1) How is the marketing strategy of umrah bayar kridit products  (2) How is the  Islamic economic review of the marketing strategy  of umrah bayar kridit products Islamic economic perspective. This type of research is qualitative descriptive field research. The subject in this study is the travel manager of Risma Tour. While the object is the implementation of the marketing strategy of Umrah products from an Islamic economic perspective. Data collection techniques use observation, interview and documentation methods and use interactive qualitative data analysis techniques. The results obtained from this study  are: (1) The marketing strategy  of Umrah bayar kridit  products is carried out by applying three things, namely: (a) Products, by providing safe and quality Umrah services, (b) Prices, by offering cheap and affordable prices, (c) Promotion, by advertising products through social media, (d) Places, by choosing locations that are easily accessible to prospective Umrah pilgrims. (2) The marketing strategy  of Umrah bayar kridit products according to Islamic economic reviews is correct, because it does not contradict the principles of Islamic teachings by using murabahah contracts in the concept of muamalah